Constitutional development in Islamic states with a special emphasis on the case of Turkey - Kayadibi, Saim (University of Malaya (UM), 2008)
The concept of constitution and the constitutional process in Islamic states lasted centuries to formulate their legal structures. One of the most significant concepts of law that is affected by social and political developments is the constitutional law. The constitutional structure of Islamic states, especially Gulf States, are considerably different than other Islamic states; Kuwait, Bahrain, Qatar, and UAE have written constitution in acknowledgeable in modern form somewhat Saudi Arabia and Oman have no written constitution stated strongly by King or Sultan and principally by the Shari‘ah. This paper tries to analyze constitutional developments in Islamic states in two main frameworks: the first deals with historical backdrops of constitutional process in Islamic states focusing on the structure of their current constitutions, while the second probes the Ottoman Turkey giving a special attention to the new Turkey, a secular state.